2019
DOI: 10.1002/ccd.28105
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post‐procedural minimal stent area on 2‐year clinical outcomes in the SYNTAX II trial

Abstract: Objectives To investigate the impact of minimal stent area (MSA) evaluated by post‐procedural intravascular ultrasound (IVUS) on clinical outcomes after contemporary PCI in patients with three‐vessel disease (TVD). Background The impact of post‐procedural MSA on clinical outcomes has not yet been extensively studied in patients with TVD. Methods The SYNTAX II study is a multicenter, all‐comers, open‐label, single arm study that investigated the impact of a state‐of‐the‐art PCI strategy on clinical outcomes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…State of the art in OCT MSA, a consistent predictor of long-term PCI outcomes 3,[44][45][46][47][48][49][50] . OCT software provide automatic measurement of stent diameter and expansion and detection of underexpanded segments.…”
Section: Medial Dissectionmentioning
confidence: 99%
See 1 more Smart Citation
“…State of the art in OCT MSA, a consistent predictor of long-term PCI outcomes 3,[44][45][46][47][48][49][50] . OCT software provide automatic measurement of stent diameter and expansion and detection of underexpanded segments.…”
Section: Medial Dissectionmentioning
confidence: 99%
“…The OPINION trial and previous studies have shown that EEL-based stent sizing strategies result in the selection of larger diameter balloons and stents and more frequent post-dilation compared with lumen-based diameter measurements 100,101 . As lower MSA has consistently been shown to be a pre-eminent cause of late DES failure 3,[44][45][46][47][48][49][50] , the difference in stent sizing strategy in these previous studies may have been a disadvantage for OCT in comparison with IVUS. The ILUMIEN III trial 21 compared OCT-, IVUS-, and angiography-guided PCI using an EEL-based sizing strategy in the OCT arm.…”
Section: Oct Versus Ivus Versus Angiography In Registries and Randomised Trialsmentioning
confidence: 99%
“…IVUS findings provide important information to physicians before and after coronary stenting. For example, the minimal stent area (MSA) among the IVUS parameters is known to be a predictor of a long-term major adverse cardiovascular event (MACE) 1)2). Until now, IVUS-guided PCI has been classified as Class IIa for a left main (LM) PCI or stent optimization in the American College of Cardiology/American Heart Association (ACC/AHA) and European Society of Cardiology (ESC) guidelines 3)4).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in our hospital, the optimal stenting endpoint (minimal stent area > 5.5 mm 2 ) is decided using IVUS imaging and is based on evidence from previous studies. 21,22 In three VLST cases of this study, the optimal stenting from the findings of the quantitative coronary angiography (QCA) and IVUS at the index PCI procedure was observed; however, in the other eight ST cases, malapposition and stent deformation were observed. All VLST cases had been prescribed with single antiplatelet therapy (aspirin 100 mg/day) at event occurrence, and two VLST cases had discontinued all antiplatelet therapy due to active bleeding.…”
Section: Risk Factors Of Clinically Indicated Tlrmentioning
confidence: 75%